PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Nurlatifah, Nurlatifah; Tugiantoro, Tugiantoro (Accounting Research and Business Journal, 2025)
This study aims to determine the effect of Capital Structure, Profitability, and Company Size on the Value of Pharmaceutical Manufacturing Companies in the 2017-2022 period. The data used in this study are secondary data with a purposive sampling technique. Seven companies were selected as samples of Pharmaceutical Manufacturing Companies. The research method used in this study is multiple linear regression with the prerequisite of classical assumption test, followed by partial significance using the hypothesis test, namely the t test, while to determine the simultaneous effect using the F test with a significance level of 5%. This study shows partial results (T test) by obtaining the results of Capital Structure (DER) having a positive and significant effect on Company Value, Profitability has no significant effect on Company Value, and Company Size has a negative and significant effect on Company Value. And for the simultaneous research results (F test) shows the results of Capital Structure (DER), Profitability (ROA), and Company Size together have an effect on Company Value. In addition, the predictive ability of the three independent variables on company value is seen from the coefficient of determination value of 54.7%. The remaining 45.3% is explained by other variables not fully considered in the research model.